Development of Flower Morphology E-Module Based on Tretes Waterfall Biodiversity to Improve Botanical Literacy And Communication Skills - Amalia Shaleha Putri; Sulisetijono Sulisetijono; Ibrohim Ibrohim (Universitas Labuhanbatu, 2025)
Background: Botanical literacy and communication skills are critical 21st-century competencies, yet they remain underdeveloped among Biology Education students. This study addresses this gap by developing and validating a flower morphology e-module that integrates local potential from the Raden Soerjo Natural Park. Methodology: Following the Lee & Owens development model, data were collected from 3 expert validators and students in one-to-one (n=3), small group (n=10), and field trials (n=32) using Likert scales, essay questions, and observation sheets. Findings: The e-module was rated